DEVELOPING SYLLABUS OF ARABIC LANGUAGE’S PRODUCTIVE COMPETENCE BASED ON CONTENT LANGUAGE INTEGRATED LEARNING (CLIL) - Yumna Rasyid; Puti Zulharby (Program Pascasarjana Universitas Negeri Jakarta, 2017)
The objective of this research is to acquire deep understanding of the developing syllabus of Arabic language’s productive competence based on content language integrated learning at Arabic language teaching department. Focus of this research is: the model of syllabus of Arabic language productive competence. This research was conducted from July 2015 until February 2016 .The research method used in this study is a research development with a qualitative approach to content. The approach used in analyzing the analysis of students need. The research instrument is the researcher herself who is equipped with table analysis. The result showed that Based on an analysis of documents of syllabus productive skills that are currently used in the Department of Arabic Language and Literature, State University of Jakarta focusing on the themes that have been determined for each meeting. How syllabus like this had not yet shown the achievements of the expected learning, so that the study sought to develop a syllabus based on the needs of learners with the approach of the syllabus-based CLIL (Content Language Integrated Learning).